Asymmetric Synthesis of Tetrahydroquinolines via Saegusa‐type Oxidative Enamine Catalysis/1, 5‐Hydride Transfer/Cyclization Sequences. Issue 4 (5th March 2014) - Suh, Chang Won; Woo, Saet Byeol; Kim, Dae Young
Abstract Enantioselective organocatalytic synthesis of tetrahydroquinolines has been achieved via Saegusa‐type oxidative enamine catalysis/1, 5‐hydride transfer/cyclization sequences. The feature of this research is a one‐pot transformation of 3‐aryl aldehydes into tetrahydroquinolines by using environmentally benign catalytic Saegusa oxidation and highly efficient internal redox reactions. The synthetically useful ring‐fused tetrahydroquinoline derivatives were obtained in moderate yields and high levels of enantioselectivity.